Incidence of radiation induced sarcoma attributable to radiotherapy in adults: A retrospective cohort study in the SEER cancer registries across 17 primary tumor sites. (February 2021) - Snow, Anson; Ring, Alexander; Struycken, Lucas; Mack, Wendy; Koç, Melissa; Lang, Julie E.
Highlights: Radiation-induced sarcomas are relatively rate event. Breast cancer had a higher risk of developing RIS compared to other solid tumors. Further studies are needed to delineate why breast cancer treatment may increase the risk for RIS. Abstract: Background: Previous studies have noted the incidence of radiation-induced sarcomas (RIS) but have not investigated the relative risk (RR) of developing RIS based on primary tumor organ disease site. By examining data from the Surveillance, Epidemiology, and End Results (SEER) database, we hypothesized that breast cancer would have a higher incidence of RIS compared to seventeen other primary cancer sites. Methods: This was a retrospective cohort study that examined patients from SEER registries between 1973 and 2013. We included patients aged 18 years or older who were diagnosed with cancer and those diagnosed with a cancer who subsequently developed a sarcoma. We excluded patients with missing information on initial radiotherapy treatment or stage. RIS was defined as those who developed a secondary sarcoma near the site of their original malignancy and after a 24-month latency period. Results: Our patients had a mean age of 60 years and follow up time of 9.2 years. Breast cancer comprised the majority with 693, 701(36.8%) patients of which 161 (0.02%) had a secondary sarcoma. Of the 359 patients with secondary sarcomas, 242 (67.4%) had RIS. Breast cancer had the highest number of RIS patients at 126 compared to all combined non-breast cancer sites at 116. The RR of RIS in breast cancer versus 19 other primary cancer sites was 1.21 (CI: 1.01–1.45, p  < 0.03, adjusted for age at primary diagnosis, gender, and latency). Conclusions: Our study demonstrated that breast cancer has a higher risk of developing RIS compared to other solid cancers.